Program for Learning in Accordance with Needs - Flanagan, John C.; American Educational Research Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
The goals of Project PLAN (Program for Learning in Accordance with Needs) are: (1) to identify and define the needs of young people between the ages six and 18, and (2) to develop procedures to enable these people to acquire identified and defined knowledge, attitudes, skills and appreciations. Also included are the specific goals of the school district whose students are participating in the Project. The system established to achieve the defined goals contains the following components: (1) a comprehensive set of educational objectives, (2) a teaching-learning unit that acts as a guide for achieving these objectives, (3) a set of tests that indicates whether or not students mastered the objectives, (4) guidance and individual planning, and (5) evaluation using an IBM 360 MODEL 50 computer. Project PLAN demonstrates the possibilities of an individualized system of instruction using the computer as an aid and resource to the teacher. Further research needs were indicated. (LS)
ERIC Note: Paper presented at the American Educational Research Association Meetings, Chicago, Illinois, February 5-8, 1968.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Programs; Instructional Design; Instructional Innovation; Learning Processes; Learning; Needs